Pertumbuhan Stek Krisan (Chrysanthemum morifolium (L.) Ramat) pada Berbagai Media Kultur In Vitro - Adven Kristianti; Kamsinah Kamsinah; Murni Dwiati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Chrysanthemum (Chrysanthemum morifolium (L.) Ramat is one of ornamental plant commodities with high aesthetic value. As a consequence of increasing demand, the availability of seeds in adequate number is needed with method in vitro. This study aims to find out the effect of various in vitro culture media on the growth of chrysanthemum explants and to determine alternative media other than MS for in vitro growth of chrysanthemum explants. Experimental method arranged in a Randomized Complete Block Design (RCBD) with four treatments and four blocks is applied. The treatments are Murashige and Skoog  (MS), Vacint and Went  (V&W), Knudson  and   modified media, while node position serves as block. Time of shoot emergence, shoot length, number of leaves on each shoot, and number of roots are measured. Data are analyzed using Analysis of Variance (F test) with confidence intervals of 95% and 99%. Least Significant Difference (LSD) test is applied when significant difference among variables is observed. Culture media shows significant effect on chrysanthemum explant in vitro growth. Knudson media is found as an alternative media besides MS sufficiently suitable to increase chrysanthemum explants in vitro growth.